Humanisme Religius dalam Pendidikan: Dialog Filsafat Pendidikan Islam dan Barat melalui Tinjauan Literatur Kritis. - Rinaldi, Tofan; Khoiriyah (JDP (JURNAL DINAMIKA PENDIDIKAN), 2026)
Contemporary education faces a growing crisis of value orientation due to the dominance of utilitarian and technocratic paradigms that prioritize cognitive achievement while marginalizing moral and spiritual dimensions. This study aims to formulate a conceptual framework of religious humanism in education through a critical dialogue between Islamic and Western philosophies of education. Using a qualitative approach with a critical-dialogical literature review (integrative review), this study analyzes selected classical and contemporary scholarly works from both traditions. The findings indicate that Western educational humanism emphasizes rational autonomy, critical thinking, and social justice, yet often neglects transcendental aspects of human development. Conversely, Islamic educational philosophy views humans as rational and spiritual beings, with education oriented toward the formation of morally grounded and civilized individuals (insān ādabī). This study argues that the dichotomy between secular humanism and religious education is artificial and can be transcended through a dialogical synthesis. It concludes that religious humanism offers a holistic educational paradigm integrating rationality, ethics, and spirituality, making it relevant for addressing contemporary educational challenges.